Locus of Control and Consistent Investment Choices - Pia Pinger; Sebastian Schäfer; Heiner Schumacher (Institute of Labor Economics (IZA), 2018)
We document that an internal locus of control can be hindering in financial market situations, where short-term outcomes are determined by chance. The reason is that internally controlled individuals may tend to (over-)react to random outcomes. Our evidence is based on an experiment in which subjects repeatedly invest in two identical, uncorrelated, risky assets and observe previous outcome realizations. Under mild restrictions, the optimal strategy is to make the same choice in each period. Yet, internals are more likely to make inconsistent risk choices. The effect size of locus of control is comparable with that of cognitive ability. Among inconsistent subjects, average switching behavior is in line with the gambler's fallacy. However, choices of very internally controlled individuals tend to correspond to the hot hand fallacy.
Keywords: D03; G02; C91; 330; locus of control; risk preferences; investment decisions; cognitive ability